Novel UV Spectroscopic Methods for Simultaneous Assessment of Empagliflozin, Linagliptin and Metformin in Ternary Mixture - Sen, Ashim Kumar; Pandey, Harshita; Maheshwari, Rajesh A.; Zanwar, Aarti Sachin; Velmurugan, Ramaswamy; Sen, Dhanya B. (Indian Journal of Pharmaceutical Education and Research, 2022)
Background and Aim: Trijardy XR® consisting of empagliflozin, linagliptin, and metformin hydrochloride, a fixed-dose combination (tablets) that improves glycemic control in individuals with diabetes mellitus (type 2). The present work presents four spectrophotometric methods that are quick, effortless, accurate and reproducible for the concurrent assessment of the ternary mixture. Materials and Methods: The 1st approach works on the principle of solving established equations (simultaneous) by measuring absorbance at 224.6, 226 and 237.2 nm for empagliflozin, linagliptin and metformin hydrochloride, respectively. The second method namely ratio difference spectroscopy works by measuring the difference in amplitude at two different wavelengths in the ratio spectra. Whereas, the derivative ratio spectrum zero-crossing approach (third approach) relied on the utilization of the derivative ratio signals at zero-crossing locations. The fourth approach is the double divisor-ratio spectra derivative approach in which the first derivative of ratio spectrum was acquired and the concentrations of all 3 drugs in their combination were quantified. Results and Discussion: All the three drugs exhibited excellent linear correlation in the concentration series of 2-10 μg/ml for simultaneous equation method and 0.5-10 μg/ml for all the other methods with an exceptional correlation coefficient value. Furthermore, the projected approaches were validated as per ICH strategies and which displayed good precision, accuracy and sensitivity. Conclusion: The developed spectrophotometric approaches when compared to other analytical procedures are regarded to be more cost-effective because they do not require expensive solvents or sophisticated instruments. Therefore, the projected methods could be effectively employed for the concurrent assessment of empagliflozin, linagliptin and metformin hydrochloride in ternary mixture.
Keywords: Empagliflozin; Linagliptin; Metformin; Simultaneous Equation Method; Ratio; Difference Spectroscopic method; Derivative Ratio Spectrum-Zero crossing approach; Double Divisor Ratio Spectra Derivative approach; Ternary mixture